Model Baru Penyusunan Kitab Hadis Ṣaḥīḥ (Kajian Manhaj Ibn Ḥibbān dalam Ṣaḥīḥnya) - Rifqi Muhammad Fatkhi (Refleksi: Jurnal Kajian Agama dan Filsafat, 2006)
In the treasury of Hadith literature from the time of the Companions until today, there are only a few Hadith collections explicitly and clearly stating that they are compilations of authentic Hadiths. Some of them include Ṣaḥīḥ al-Bukhārī and Ṣaḥīḥ Muslim, Ṣaḥīḥ ibn Khuzaymah, Ṣaḥīḥ ibn Ḥibbān, Ṣaḥīḥ ibn Sakan, and Ṣaḥīḥ ibn al-Syarqī. This article will provide information about Ṣaḥīḥ ibn Ḥibbān. This book is considered to have a different model of writing compared to other authentic books. Besides the systematic arrangement, the compiler also sets different criteria for the authenticity of Hadiths, unlike most Hadith scholars.